Association Between Overt Hyperthyroidism and Risk of Sexual Dysfunction in Both Sexes: A Systematic Review and Meta-Analysis. Issue 11 (13th August 2020) - Pan, Yin; Xie, Qiang; Zhang, Zhuoni; Dai, Yuechu; Lin, Lizhong; Quan, Mingming; Guo, Xiaowei; Shen, Maolei; Zhao, Shankun
Abstract: Background: Numerous studies have shown the detrimental effects of overt hyperthyroidism on sexual functioning but a quantitative result has not yet been synthesized. Aim: To conduct a systematic review and meta-analysis that quantifies the association between overt hyperthyroidism and the risk of sexual dysfunction (SD). Methods: A meta-analysis of studies in the literature published prior to February 1, 2020, from 4 electronic databases (MEDLINE, Embase, Cochrane Library databases, and PsychINFO) was conducted. All analyses were performed using the random-effects model comparing individuals with and without overt hyperthyroidism. Outcomes: The strength of the association between overt hyperthyroidism and risk of SD was quantified by calculating the relative risk (RR) and the standard mean difierences with 95% CI. The quality of evidence for the reported outcome was based on the Grading of Recommendations Assessment, Development, and Evaluation approach. Results: Of 571 publications, a total of 7 studies involving 323, 257 individuals were included. Synthetic results from 7 eligible studies indicated that overt hyperthyroidism led to significant SD in both sexes (pooled RR = 2.59, 95% CI: 1.3–5.17, P  = .007; heterogeneity: I 2  = 98.8%, P  < .001). When we analyzed the data of men and women independently, the pooled results consistently showed that men and women with overt hyperthyroidism were at over 2-fold higher risk of SD than the general populations (RR for males = 2.59, 95% CI: 1.03–6.52, P  = .044; RR for females = 2.51, 95% CI: 1.47–4.28, P  = .001). Combined standard mean diffierences from those studies providing the Female Sexual Function Index (FSFI) suggested that women with overt hyperthyroidism were associated with a significantly lower FSFI value in FSFI total scores, subscale sexual arousal, lubrication, orgasm, and satisfaction domain (all P  < .05). The overall quality of evidence in our study was considered to be moderate. Clinical Implications: Clinicians should know the detrimental effects of overt hyperthyroidism on sexual functioning in clinical practice. Measurement of thyroid hormones should be included in the assessment of patients presenting with SD when they show symptoms of clinical hyperthyroidism. Strengths & Limitations: This is the first meta-analysis quantifying the relationship between overt hyperthyroidism and the risks of SD. However, the combined results were derived from limited retrospective studies along with substantial heterogeneities. Conclusion: Our study has confirmed the potentially devastating sexual health consequences caused by overt hyperthyroidism. However, additional rigorous studies with sizable samples are still needed to better elucidate this evidence.